Left Ventricular Ejection Fraction and Risk of Stroke and Cardiac Events in Heart Failure: Data From the Warfarin Versus Aspirin in Reduced Ejection Fraction Trial. Issue 8 (August 2016) - Di Tullio, Marco R.; Qian, Min; Thompson, John L.P.; Labovitz, Arthur J.; Mann, Douglas L.; Sacco, Ralph L.; Pullicino, Patrick M.; Freudenberger, Ronald S.; Teerlink, John R.; Graham, Susan; Lip, Gregory Y.H.; Levin, Bruce; et al.
Abstract : Background and Purpose—: In heart failure (HF), left ventricular ejection fraction (LVEF) is inversely associated with mortality and cardiovascular outcomes. Its relationship with stroke is controversial, as is the effect of antithrombotic treatment. We studied the relationship of LVEF with stroke and cardiovascular events in patients with HF and the effect of different antithrombotic treatments. Methods—: In the Warfarin Versus Aspirin in Reduced Ejection Fraction (WARCEF) trial, 2305 patients with systolic HF (LVEF⩽35%) and sinus rhythm were randomized to warfarin or aspirin and followed for 3.5±1.8 years. Although no differences between treatments were observed on primary outcome (death, stroke, or intracerebral hemorrhage), warfarin decreased the stroke risk. The present report compares the incidence of stroke and cardiovascular events across different LVEF and treatment subgroups. Results—: Baseline LVEF was inversely and linearly associated with primary outcome, mortality and its components (sudden and cardiovascular death), and HF hospitalization, but not myocardial infarction. A relationship with stroke was only observed for LVEF of <15% (incidence rates: 2.04 versus 0.95/100 patient-years; P =0.009), which more than doubled the adjusted stroke risk (adjusted hazard ratio, 2.125; 95% CI, 1.182–3.818; P =0.012). In warfarin-treated patients, each 5% LVEF decrement significantly increased the stroke risk (adjusted hazard ratio, 1.346; 95% CI, 1.044–1.737; P =0.022; P value for interaction=0.04). Conclusions—: In patients with systolic HF and sinus rhythm, LVEF is inversely associated with death and its components, whereas an association with stroke exists for very low LVEF values. An interaction with warfarin treatment on stroke risk may exist. Clinical Trial Registration—: URL:http://www.clinicaltrials.gov . Unique identifier: NCT00041938. Abstract : Supplemental Digital Content is available in the text.